Demokrasikita.id sebagai Bagian dari Civil Society dalam Penguatan Demokrasi Lokal di Kota Bandung - Syaira Diasyifa Herlambang; Muhammad Alfian Zuhri; Muradi Muradi (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
Demokrasikita.id was established as a civil society initiative aimed at enhancing the quality of local democracy, particularly in anticipation of the Bandung City Regional Election. The emergence of demokrasikita.id is a form of criticism of the tendency of participants in the local political process, where the political agenda is often dominated by party elites and certain interests. This study uses a qualitative approach with analysis based on civil society theory. Data collection techniques were carried out through interviews, observation, and documentation studies. The results of the study show that the role of demokrasikita.id in strengthening local democracy as a civil society covers two aspects, namely advocacy through a series of systematic stages, starting from issues to participatory forums and social control, which is realized through five aspirations resulting from the participatory process of the Bandung City Community. Meanwhile, the role of empowerment is not the focus of demokrasikita.id but is still present to complement it. In its efforts to become a forum for civil society movements, demokrasikita.id is often faced with internal and external challenges, such as the commitment of its activists to maintaining the stability and direction of the organization and how it navigates local political and social conditions that do not yet fully support the growth of deliberative public participation.